Reflective writing skills in medical students in Universiti Sains Malaysia and its associations - Mustaffa, Liyana Nadhirah (2024)
Reflective writing skills among medical students across many countries still showed limited competency in this area. However, cultivating these skills during medical training is crucial for developing good reflective practices among physicians. Previous studies have shown that reflective writing skills impact medical students' academic and clinical performance. This study aims to determine the level of reflective writing skills among medical students at Universiti Sains Malaysia (USM) and its associations with demographic factors, and academic and clinical performance. A total of 420 reflective writing documents were analysed using SPSS version 27.0, with 350 (83.3%) of the documents being randomly chosen for the study. The selected documents were sourced from first-year medical students in the batches of 2020/21, 2021/22, and 2022/23. These documents were graded by raters using the REFLECT rubric tool, designed to address the challenge of assessing these written reflections. The REFLECT rubric provides a systematic framework for the assessment of reflective writing skills, facilitating a comprehensive evaluation of this competency among medical students in USM. The demographic data collected included age, sex, pre-university education, Mini Multiple Interview (MMI) scores, and Cumulative Grade Point Average (CGPA) of the second and sixth semesters as well as Objective Structured Clinical Examination (OSCE) scores. The main outcome measured was the reflective writing score, which underwent descriptive statistical analysis to ascertain the correlation between each variable and reflective writing skills. Age was analysed using Spearman's correlation, sex was analysed using an independent t-test, and pre-university education was analysed using one-way ANOVA. MMI scores, second and sixth-semester CGPAs, and OSCE were analysed using Pearson's correlation. The average total reflective writing score for first-year medical students was 15.21 (SD = 2.18). Female students reported significantly higher total reflective writing scores (M = 15.42, SD = 2.19) and "attending to emotion" scores (M = 3.22, SD = 0.59) compared to male students (M = 14.71, SD = 2.09, and M = 2.81, SD = 0.68, respectively). The results revealed significant correlations between the first-year CGPA and several domains of reflection, including writing spectrum, description of conflict, and attending to emotion, analysis, and meaning-making, as well as overall reflective writing score The study found that reflective writing skills among medical students at Universiti Sains Malaysia were normally distributed. While age, pre-university education, and MMI scores were not significantly associated with reflective writing abilities, sex, and first-year CGPA emerged as significant factors. Female students demonstrated significantly higher reflective writing scores, particularly in the "attending to emotion" domain, compared to their male peers. Furthermore, the results revealed positive correlations between reflective writing scores and academic performance, as measured by first-year CGPA, with higher CGPAs linked to better reflective writing skills. In conclusion, the findings suggest that reflective writing skills among medical students at USM are influenced by sex, and these skills have a significant role in academic performance. Since reflective writing is a crucial skill for future doctors, measures should be taken to address potential sex-based differences in the development and execution of reflective writing courses. Moreover, fostering reflective writing skills should be prioritized as it contributes positively to students' academic success and has the potential to enhance their growth as reflective practitioners in the medical field.